Rare hereditary nonspherocytic hemolytic anemia caused by a novel homozygous mutation, c.301C > A, (Q101K), in the AK1 gene in an Indian family - Rashmi Dongerdiye; Abhilasha Sampagar; Rati Devendra; Prashant Warang; Prabhakar Kedar (BMC, 2021)
Abstract Background Adenylate kinase (AK) deficiency is a rare red cell enzymopathy associated with moderate to severe congenital nonspherocytic hemolytic anemia, along with mental and psychomotor retardation (in exceptional cases). Only ten mutations have been detected in the AK1 gene to date. In this study, we aimed to diagnose the unexplained issue of haemolytic anaemia and offer antenatal screening to the family. Methods Genomic DNA was isolated from whole blood by a standard protocol. Targeted next-generation sequencing (t-NGS) was performed to identify pathogenic variants in the patient and control samples. A chronic villus sample was collected at 11 weeks of gestation from the mother, and molecular testing was performed. Genetic confirmation was concluded by Sanger DNA sequencing. Bioinformatics tools predicted the pathogenicity of the variant. Results t-NGS revealed a homozygous variant (c.301C > A, p. Gln101Lys) in the AK1 gene in the patient and heterozygosity in the fetus and parental samples. The prediction tools SIFT, Polyphen2, Provean, PMUT, Mutation taster, and Mutation Assessor, confirmed the damaging effect of the variant on the AK1 protein structure Conclusion We have presented a novel mutation in the AK1 gene (p. Gln101Lys) associated with adenylate kinase deficiency. It is the first prenatal diagnosis of AK deficiency in India, where heterogeneity is exceptionally high.